Analysis of the effect of motivation, compensation and work environment on employee performance with competency as intervening variable at PT. Pegadaian Medan - Salman Faris; Munawwarah Munawwarah; Sofiyan Sofiyan; Syaifuddin Syaifuddin (Journal of Economics and Business Letters, 2022)
Organizational success is strongly influenced by the performance of its employees, and in improving employee performance, adequate competence and ability are needed. This study aims to determine the role of motivation, compensation, and work environment on employee performance with competency mediating variables. This study uses a quantitative approach with SPSS software and involves 65 employees of PT. Pegadaian Medan. The results of this study found that motivation, compensation, and work environment affect the performance of employees at PT. Pegadaian Medan. Competence affects the performance of employees at PT. Pegadaian Medan. Motivation, compensation, and work environment affect employee performance with competence as an intervening variable at PT. Pegadaian Medan. Companies need to increase the above variables in improving the performance of employees of PT. Pegadaian Medan.